2003
DOI: 10.1046/j.1365-2141.2003.04286.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of recombinant factor VIIa in children with inherited platelet function disorders

Abstract: Summary. Inherited deficiencies of platelet surface glycoproteins such as Glanzmann's thrombasthenia (GT) or Bernard–Soulier syndrome (BSS) can lead to a severe bleeding diathesis. In the past, bleeding episodes in these patients have often required platelet transfusion to secure haemostasis but recently a number of patient reports have suggested that recombinant factor VIIa (rVIIa) may also be effective. We have used rVIIa on 33 occasions in seven children with inherited platelet function disorders over a 2‐y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
123
0
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(133 citation statements)
references
References 20 publications
2
123
0
8
Order By: Relevance
“…In one series of patients, the use of factor VIIa was reported to be effective in about 48% of patients. 50 …”
Section: Glanzmann Thrombastheniamentioning
confidence: 99%
“…In one series of patients, the use of factor VIIa was reported to be effective in about 48% of patients. 50 …”
Section: Glanzmann Thrombastheniamentioning
confidence: 99%
“…In a large international survey, rFVIIa treatment was found to be effective in 94% of evaluable surgical procedures and in 75% of evaluable bleeding episodes 2 . It is also recommended that treatment should be administered as early as possible: in the report of Almeida et al 5 good or excellent responses were observed in 71% of bleeds treated within 12 hours of onset, but in only 18% of bleeds treated after 12 hours.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Almeida et al 5 , a single dose of 100 µg.kg -1 was given in bleeding episodes of two children with GT, and because of an excellent response, they required no maintenance dose 5 . We also achieved to maintain the adequate homeostasis with early use of a single low-dose rFVIIa such as 60 µg.kg -1 additional to preoperative platelet transfusion in our GT patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We advise the administration of HLA-matched platelets for these patients wherever possible. One strategy for haemostasis management of conditions such as Glanzmann's thrombasthenia (see below), has been the use of recombinant factor VIIa which exerts at least some of its haemostatic effect through direct activation of coagulation, and which can be effective in some situations [44]. It would not, however be recommended for major surgery in severe disorders [45], as the effects are difficult to predict and assess, and there may be significant associated thrombotic risks.…”
Section: Inherited Platelet Function Disordersmentioning
confidence: 99%